ЕLECTROMAGNETIC FIELD EQUATIONS IN NONLINEAR ENVIRONMENT - Lyshuk, Viktor; Tchaban, Vasyl; Tkachuk, Anatolii; Zablotskyi, Valentyn; Selepyna, Yosyp (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The paper proposes electromagnetic field equations from the point of view of their adaptation to numerical methods. Maxwell’s equations with partial derivatives are used, written concerning field vectors, which most fully reproduce the picture of physical processes in electrical engineering devices. The values of these vectors provide comprehensive information about the field at any spatio-temporal point. The concept of creating mathematical models of electrical devices adequate to physical processes has been developed. Mathematical transformations are carried out according to the rules of differential calculus. Dynamic processes in the elements of electrotechnical devices were analyzed using the apparatus of mathematical modeling. An algorithm for implementing differential equations with partial derivative numerical methods using computer simulation was implemented. The obtained results made it possible to understand the nature of electromagnetic phenomena in nonlinear media. The paper provides calculations of the field parameters in a flat ferromagnetic plate and the groove of the rotor of an electric machine.